J08 The oral health and dental treatment of adults with Huntington's disease. (16th November 2010) - Lane, H; Manley, G
Abstract : Background: The Royal Hospital for Neuro-Disability (RHN) is the largest provider of care for people with advanced-stage HD in the UK. A dental department within the hospital provides oral health care for the residents. Aim: To investigate the oral health and oral health care of people with HD within the hospital. Methods: An audit of the oral health of individuals with mid-late stage HD. An account of the treatment provided. Results: When compared to the UK general population, people with HD: had more decayed teeth, less filled and more extracted teeth. had teeth that were less clean. were taking medication which can cause dry mouth. Dental treatment 66% required dental treatment. 60% received intravenous sedation to enable dental treatment. Outcome: The oral health of people with late stage Huntington's disease is significantly poorer than that of people who do not have this condition. Treatment for this group requires special skills, (eg, use of intravenous conscious sedation), flexibility of care and should be provided safely within the context of progression of the condition. Conclusions: To create guidelines to assist in the development of standards of oral health care for people with HD. To investigate the oral health and oral health care needs of people with early stage HD. Encourage multi and inter-disciplinary management practices for people with HD that include the dental team.